Views and Experiences of Pre-Service Science Teachers on the Use of Technology in Teaching and Learning of Electric Concepts - Nyangiwe Nandipha; Mmushetji Rankhumise; Thomas Sedumedi (Unnes Science Education Journal, 2023)
The aim of the study was to explore pre-service science teachers’ views and experiences on the use of technology in teaching and learning of electric concepts. . The study sample consisted of six pre-service science teachers enrolled in Physical Science level 1 at a university of technology in South Africa, who aspire to be Physical Science teachers, and whose curriculum consist of electricity. The study adopted a case study research design embedded within the qualitative research approach. Data for the study was collected voluntarily from participants in alignment with the convenience sampling technique. The results of the study indicate the need for educators to have technology integration strategies because some schools lack equipment needed to conduct experiments. Moreover, pre-service science teachers recommend the use of technology integration because it is cheaper, safer, and more convenient